Limiting Cosines of Singular Double Triple

Calculus Level 4

lim x 0 1 cos ( x ) cos ( 2 x ) ( cos ( 3 x ) ) 1 3 x 2 \large \lim_{x\to 0} \frac{1- \cos(x) \sqrt{\cos(2x)} (\cos(3x))^{\frac{1}{3}}}{x^{2}}

Evaluate the limit above without using L'Hôpital rule.


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

To evaluate this limit,we will use the expansions of cos ( x ) , cos ( 2 x ) & cos ( 3 x ) \cos(x) , \cos(2x) \text{ \& } \cos(3x)

cos ( x ) = 1 x 2 2 ! + x 4 4 ! \cos(x) = 1 - \dfrac{x^2}{2!} + \dfrac{x^4}{4!} \ldots

cos ( 2 x ) = 1 4 x 2 2 ! + 16 x 3 4 ! \cos(2x) = 1 - \dfrac{4x^2}{2!} + \dfrac{16x^3}{4!} \ldots

cos ( 3 x ) = 1 9 x 2 2 ! + 81 x 4 4 ! \cos(3x) = 1 - \dfrac{9x^2}{2!} + \dfrac{81x^4}{4!} \ldots

We neglect higher power terms like x 4 , x 6 , x^4, x^6, \ldots

lim x 0 1 ( 1 x 2 2 ) ( 1 2 x 2 ) 1 2 ( 1 9 x 2 2 ) 1 3 x 2 \displaystyle \lim_{x \to 0} \dfrac{1 - \left(1 - \frac{x^2}{2} \right)\left(1 - 2x^2\right)^{\frac{1}{2}}\left(1 - \frac{9x^2}{2}\right)^{\frac{1}{3}}}{x^2}

Now as x 0 , ( 1 + x ) n ( 1 + n x ) x \to 0, (1+x)^n \approx (1+nx)

lim x 0 1 ( 1 x 2 2 ) ( 1 x 2 ) ( 1 3 x 2 2 ) x 2 \displaystyle \lim_{x \to 0} \dfrac{1 - \left(1 - \frac{x^2}{2}\right)\left(1 - x^2\right)\left(1 - \frac{3x^2}{2}\right)}{x^2}

lim x 0 1 ( 1 x 2 2 x 2 ) ( 1 3 x 2 2 ) x 2 \Rightarrow \displaystyle \lim_{x \to 0} \dfrac{1 - \left(1 - \frac{x^2}{2} - x^2\right)\left(1 - \frac{3x^2}{2} \right)}{x^2}

lim x 0 1 ( 1 x 2 x 2 2 3 x 2 2 ) x 2 \Rightarrow \displaystyle \lim_{x \to 0} \dfrac{1 - \left(1 - x^2 - \frac{x^2}{2} - \frac{3x^2}{2} \right)}{x^2}

lim x 0 ( x 2 ) ( 1 2 + 1 + 3 2 ) x 2 \Rightarrow \displaystyle \lim_{x \to 0} \dfrac{(x^2)(\frac{1}{2} + 1 + \frac{3}{2})}{x^2}

1 2 + 1 + 3 2 = 3 \Rightarrow \displaystyle \dfrac{1}{2} + {1} + \dfrac{3}{2} = \boxed{3}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...